2016
DOI: 10.1080/09585192.2016.1244911
|View full text |Cite
|
Sign up to set email alerts
|

Espoused versus realized knowledge management tool usage in knowledge intensive organizations

Abstract: Espoused versus realized knowledge management tool usage in knowledge intensive organizations Many knowledge intensive organizations (KIOs) have invested in tools and policies to enhance knowledge-sharing and application as this is crucial for their growth. The implementation of these tools results in multiple approaches for knowledge-sharing being available. This article reports on an empirical study of five global management consultancies investigating how consultants choose between these knowledge-sharing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 53 publications
(66 reference statements)
0
7
0
Order By: Relevance
“…Studies within this sub-area are highly focused on the development of models for an efficient knowledge system (Werr and Stjernberg, 2003;Anand et al, 2007). An empirical study of five global management consultancies, investigating how consultants choose between different knowledge-sharing systems, found that different criteria are adopted by the leadership of the MCF and the consultants, so that when considering knowledge management (KM) tools it was critical to take a multi-level approach (Powell and Ambrosini, 2017). Haas and Hansen (2005) added that competitive performance depends not only on how much MC companies know but also on how they use what they know.…”
Section: Drivers Of Management Consulting Successmentioning
confidence: 99%
“…Studies within this sub-area are highly focused on the development of models for an efficient knowledge system (Werr and Stjernberg, 2003;Anand et al, 2007). An empirical study of five global management consultancies, investigating how consultants choose between different knowledge-sharing systems, found that different criteria are adopted by the leadership of the MCF and the consultants, so that when considering knowledge management (KM) tools it was critical to take a multi-level approach (Powell and Ambrosini, 2017). Haas and Hansen (2005) added that competitive performance depends not only on how much MC companies know but also on how they use what they know.…”
Section: Drivers Of Management Consulting Successmentioning
confidence: 99%
“…Although these studies did not provide direct evidence on the content of HRM in PSF, we examined how HRM practices were conceptualized and measured, which was also useful for further systematization. Another type of papers that we did not directly use in our analysis was studies that focused on employee behavior rather than HRM (Segal-Horn and Dean, 2007; Donnelly, 2011a, b; Kinnie and Swart, 2012; Frey et al , 2013; Sparrow et al , 2013; Bevort and Poulfelt, 2015; George, 2015; Powell and Ambrosini, 2017). These articles only briefly discussed the content of HRM practices but were useful for creating more holistic picture of the subject of this study.…”
Section: Resultsmentioning
confidence: 99%
“…The authors argue that firms alter their approach to knowledge management based on contextual and learning-based reasons. In line with this, Powell and Ambrosini (2017) have emphasized the importance of the pluralistic approach while studying how management consultants choose between knowledge transfer alternatives and the factors driving their choices. The authors have found that the leadership and the consultants have different perspectives on the perceived value of different knowledge transfer approaches.…”
Section: Contrary Tomentioning
confidence: 98%
“…Leadership emphasizes increased reach and rapid search, while the consultants find social networks to be superior. Powell and Ambrosini (2017) argue that the consultants base their decisions on the perceived benefits of the knowledge content and the estimated process costs. Thus, when choosing knowledge management tools, it is important to consider implementing multiple approaches as there might be differences in the motives for why some tools are used while others are not.…”
Section: Contrary Tomentioning
confidence: 99%